ANTIBACTERIAL AND BIODEGRADATION NATURE TEST OF EDTA-Ag IMMOBILIZED SILICA COMPOZITE PLASTICS AND CHITOSAN - Wogo, Hermania Em; Ndoen, Martha C. W.; Ola, Pius Dore (Chemistry Notes, 2019)
It has been conducted a research, which it aims to know the antibacterial and biodegradation nature of EDTA-Ag and chitosan immobilized silica composite plastics. Silica used was from rice hull processing products. Chitoson used was 0.3 and 0.7 g. Antibacterial assay was conducted over Staphylococcus aureusandEscherichia coli bacteria. the result obtained showed that the biggest inhibitory is at variation of chitosan 0.7 g, which over Staphylococcus aureusbacteria is 15.6 mm and Escherichia colibacteria is 16,7 mm. While, in biodegradation assay, the highest degradation percentage is at chitosan variation 0.3 g, namely 32.17%.